Sunday

December 21, 2014

December 21, 2014

Posted by **Quetzally** on Thursday, March 8, 2012 at 9:04am.

csc^4 x-cot^4x= Csx^2 x + cot^2x

- Trig -
**Steve**, Thursday, March 8, 2012 at 12:22pmrecall that a^2 - b^2 = (a+b)(a-b)

csc^4 - cot^4 = (csc^2 - cot^2)(csc^2 + cot^2)

if you recall that csc^2 = 1 + cot^2 the rest is downhill. . .

**Answer this Question**

**Related Questions**

trig - For each expression in column I, choose the expression from column II to ...

Math - Trig - I'm trying to verify these trigonometric identities. 1. 1 / [sec(x...

trig - prove the identity: csc x-1/csc x+1 = cot^x/csc^x+2 csc x+1

trig - prove the identity sec^2x times cot x minus cot x = tan x

trig 30 - For csc^2 A-1/cot A csc A, what is the simplest equivalent trig ...

Trigonometry - Use the trig Identities to find the other 5 trig functions. ...

Pr-Cal/Trig - 1)if the graph of f(x)=cotx is transformed by a horizontal shrink ...

Calculus - integral of cscx^(2/3)(cot^3)x i know that cot^2x is csc^2(x)-1, but ...

trig - verify : [sec(x) / csc(x) - cot(x)] - [sec(x) / csc(x) + cot(x)] = 2csc(x...

trig - Derive the identity 1 + cot ^2 theta = csc^2 theta by dividing x^2 + y^2...